(untitled) (Revista de Estudos da Linguagem, 2024)
Studies in Chinese-Portuguese interpreting (Lopes, 2018; Zhou; Sun, 2020) have gained increasing attention in recent years. The present study aims to explore to what extent environment and task characteristics (Chen, 2017) may influence the cognitive load of consecutive interpreting. Based on an adaptation of the criteria proposed by Skehan (2003), the current study assesses cognitive load through disfluencies, with the focus on statistical correlations between fluency and influential factors. Among the examined features, we found the order and duration of the interpreting round, the direction of interpreting, the location and the gender of the source-speech speaker are statistically influential on the interpreting fluency, in decreasing order of importance, while the speed of the source-speech shows no significant correlation with fluency. The study shows the statistically significant indicators for interpreting fluency and suggests the possible explanations, contributing to a better understanding of the cognitive load in Chinese-Portuguese consecutive interpreting and encourages future studies in the area in adopting disfluencies as a tool in assessing cognitive load.